1991
DOI: 10.1002/ptr.2650050114
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ginsenoside Rg1 on insulin binding in mice liver and brain membranes

Abstract: The effect of in uiuo administration of ginsenoside Rgl from Pumux ginseng on insulin binding in liver and brain membranes of mice was studied. Ginsenoside Rg, at a dose of 10mg/Lg significantly increased ['zsI]insulin binding in both tissues. The increase in insulin binding was related to an increase in the number of insulin receptors rather than to a change in the receptor affinity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…17 Insulin binding in rat liver, brain, and bone marrow was also increased by ginsenoside Rg1 or Asian ginseng extract. [18][19] The third possible mechanism, modulation of glucose transport, suggests that ginseng extracts and compounds may increase glucose transport in various cell lines. In the livers of mice, glucose transporter (GLUT)-2 protein expression was increased by Asian ginseng extract.…”
Section: Discussionmentioning
confidence: 99%
“…17 Insulin binding in rat liver, brain, and bone marrow was also increased by ginsenoside Rg1 or Asian ginseng extract. [18][19] The third possible mechanism, modulation of glucose transport, suggests that ginseng extracts and compounds may increase glucose transport in various cell lines. In the livers of mice, glucose transporter (GLUT)-2 protein expression was increased by Asian ginseng extract.…”
Section: Discussionmentioning
confidence: 99%
“…Another important biological effect reported for Panax ginseng or its saponins is hypoglycemic and antihyperglycemic activity (133,134). It has been shown that ginsenoside Rg1 increased the number of insulin receptors (135) and panaxan B, the main constituent of Panax ginseng for hypoglycemic activity, increased the plasma insulin level and enhanced insulin sensitivity (133). Ginseng also shows anti-stress activities against physical (i), chemical (ii), and biological (iii) stressful circumstances.…”
Section: Other Pharmacological Effects Of Ginsengmentioning
confidence: 99%
“…Ginsenoside Rg 1 was reported to increase the number of insulin receptors rather than to change the receptor affinity. 247 Panaxan A was also reported as a main component for hypoglycemic activity of P. ginseng. 248 Research on the mechanisms of hypoglycemic activity suggested that panaxan B increased the plasma insulin level and enhancement of insulin sensitivity, while panaxan A worked by other mechanisms.…”
Section: Antihyperglycemic Effectmentioning
confidence: 99%